Determinan Nilai Perusahaan Sektor Manufaktur di Bursa Efek Indonesia Periode 2020–2024 - Aqila Aulia; Rosdiana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to analyze the partial effect of Free Cash Flow (FCF) and Net Gearing Ratio (NGR) on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach. Firm value is measured using Price to Book Value (PBV). The research data were obtained from the annual financial reports of manufacturing companies included in the LQ45 index during the observation period. The analysis technique used was multiple linear regression supported by classical assumption testing. The results indicate that partially, Free Cash Flow has a positive effect on firm value, while Net Gearing Ratio has a negative effect on firm value. The research findings indicate that a company's ability to generate free cash flow and optimal capital structure management are important factors in shaping investor perceptions of the company.